Magnetic stratigraphy - Opdyke, Neil D. (International geophysics series, 1996)
Magnetic Stratigraphy is the most comprehensive book written in the English language on the subject of magnetic polarity stratigraphy and time scales. This volume presents the entirety of the known geomagneticrecord, which now extends back about 300 million years. The book includes the results of current research on sea floor spreading, magnetic stratigraphy of the Pliocene and Pleistocene, and postulations on the Paleozoic. Also included are both historicalbackground and applications of magnetostratigraphy. Individual chapters on correlation are presented, using changes in magnetic properties and secular variation. Key Features * Discusses pioneering work in the use of marine sediments to investigate the Earths magnetic field * Serves as a guide for students wishing to begin studies in magnetostratigraphy * Provides a comprehensive guide to magnetic polarity stratigraphy including up-to-date geomagnetic polarity time scales * Correlates magnetic stratigraphics from marine and non-marine Cenozoic sequences * Details reversal history of the magnetic field for the last 350 million years * Discusses correlation using magnetic dipole intensity changes * Up-to-date correlation of biostratigraphy with magnetic stratigraphy through the late Jurassic.